2004
DOI: 10.1093/humrep/deh424
|View full text |Cite
|
Sign up to set email alerts
|

Roles of p38 and c-jun in the differentiation, proliferation and immortalization of normal human endometrial cells

Abstract: These results suggest that the modulation of p38 and c-jun may play an important role in the differentiation and proliferation of human endometrial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The role of c-Jun in cellular proliferation, differentiation and apoptosis is well established [57], [58]. Studies also suggest that c-Jun can regulate neo intima formation and promote the proliferation and differentiation of vascular smooth muscle cells [59] and human endometrial cells [60]. AP-1 has been shown to be involved in the activation of matrix metalloproteinase (MMP) in progressive and unstable atherosclerotic plaques [61] as well as during the early disease process [52].…”
Section: Discussionmentioning
confidence: 99%
“…The role of c-Jun in cellular proliferation, differentiation and apoptosis is well established [57], [58]. Studies also suggest that c-Jun can regulate neo intima formation and promote the proliferation and differentiation of vascular smooth muscle cells [59] and human endometrial cells [60]. AP-1 has been shown to be involved in the activation of matrix metalloproteinase (MMP) in progressive and unstable atherosclerotic plaques [61] as well as during the early disease process [52].…”
Section: Discussionmentioning
confidence: 99%
“…showed, using immunohistochemistry, that c-jun expression occurs primarily in the proliferative phase of the menstrual cycle 80 , which was further supported by Hong et al . showing a correlation between growth in cultured endometrial stromal cells and activated c-jun expression 81 .…”
Section: Expression and Localization Of E2-erα C-fos C-jun And C-mmentioning
confidence: 94%
“…This finding suggests an important regulatory role for p38 in endometrial cell growth. Indeed, a modulatory role for p38 in human endometrial stromal cell differentiation and proliferation in the uterus has been reported 81 . Growth factors from uterine stromal cells regulate the uterine epithelia, and many of them (e.g., fibroblast growth factors-7 and -10, hepatocyte growth factor) signal via p38 MAPK 87 .…”
Section: Role Of P38 Mapk Signaling In Stromal Cell Differentiation Amentioning
confidence: 99%
See 1 more Smart Citation
“…Endometrial SCs that are persistent in the uterine endometrium from the fetal to the postmenopausal period [66] were found to differentiate into adipocytes, osteoblasts and chondrocytes as well [67,68] (Figure 4). The modulation of p38 and c-jun might play an important role for the differentiation and proliferation of normal human endometrial cells [69]. These differentiations can identify by positive staining, with Oil Red O (for lipid droplets), alizarin red (for osteogenesis), von Kossa (for calcified extracellular matrix), and Alcian blue (for sulfated proteoglycans), respectively.…”
Section: Introductionmentioning
confidence: 99%